"I Don't Identify with It": A Qualitative Analysis of People's Experiences of Living with Complex Regional Pain Styndrome. Issue 12 (8th March 2021) - Antunovich, Dana; Tuck, Natalie; Reynolds, Lisa M; Bean, Debbie
Abstract: Objective: Complex regional pain syndrome (CRPS) is a painful limb condition known to cause significant disability and distress. However, little previous research has explored CRPS from a patient perspective. The present qualitative study aimed to describe the experiences of people living with CRPS. Subjects: Forty-eight people with CRPS participated in this research. Methods: Participants completed a face-to-face or telephone interview about their perceptions and experiences of CRPS and completed three drawings to illustrate their experiences. Data were analyzed through reflexive thematic analysis, and images in drawings were grouped and coded by theme. Results: Three overarching themes encapsulated the data, including that 1) people experience CRPS as a source of severe symptoms and emotional difficulties, 2) CRPS undermines personal and social identity, and 3) this results in psychological responses that protect against the emotional and social impact of severe symptoms. Psychological responses include: a) searching for an explanation, b) "nothing is my fault, " emphasizing a lack of personal responsibility and personal control, and c) detaching the limb from the self. Conclusions: CRPS is experienced as highly threatening to physical ability, psychological state, and identity. In response to these threats, people may develop their own explanations for CRPS and may mentally detach themselves from responsibility, control, and the painful limb itself. Future research could explore the impact of these factors on psychological well-being and CRPS symptoms and outcomes.